Breakthrough Effect of Combining Resource Management Models - Balashova, Elena S.; Gromova, Elizaveta A. (International Review of Management and Marketing, 2017)
Nowadays Russia is trying to overcome the difficult times, which are characterized by a complicated international situation, high level of turbulence in social and economic sphere and general uncertainty. In the conditions of extremely fierce competition, companies prefer to use a combination of business models with the aim to take the best from several concepts of management. The goal of this research is to analyze one of the model of modern resource management – «velocity» and to relate it to the current state of the Russian economy. Theoretical and practical aspects of the model are presented. Implementation of the «velocity» in the UEC - Gas Turbines, Joint-stock Company is highlighted. This is one of the few examples of using above-mentioned concept in Russia. Summarizing, «velocity» can become a promising strategy in the context of the Russian economic situation and in general in the contemporary conditions of the world economic development. Keywords: velocity, lean production, theory of constraints, six sigma, resource management. JEL Classifications: D22, L23, M11